2019
DOI: 10.1016/j.jare.2019.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of carbapenem-resistance in Shewanella algae by CRISPR/Cas9 genome editing

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 49 publications
1
25
0
3
Order By: Relevance
“…These results indicate that CRISPR/Cas9-mediated DSBs and HDR efficiently introduced a site-directed mutation in the MR-1 genome. The frequency of CRISPR/Cas9-mediated mutations observed here is equal to or greater than those of Shewanella algae and other bacteria (Liu et al, 2017;Oh and van Pijkeren, 2014;Wu et al, 2019). A previous study has reported that DNA damage induces the up-regulation of genes involved in homologous recombination in MR-1 (Qiu et al, 2006), supporting that HDR after CRISPR/Cas9-mediated DSB occurs at a high frequency in this strain.…”
Section: Induction Of Dsbs and Hdr In Mr-1 By Crispr/cas9supporting
confidence: 67%
“…These results indicate that CRISPR/Cas9-mediated DSBs and HDR efficiently introduced a site-directed mutation in the MR-1 genome. The frequency of CRISPR/Cas9-mediated mutations observed here is equal to or greater than those of Shewanella algae and other bacteria (Liu et al, 2017;Oh and van Pijkeren, 2014;Wu et al, 2019). A previous study has reported that DNA damage induces the up-regulation of genes involved in homologous recombination in MR-1 (Qiu et al, 2006), supporting that HDR after CRISPR/Cas9-mediated DSB occurs at a high frequency in this strain.…”
Section: Induction Of Dsbs and Hdr In Mr-1 By Crispr/cas9supporting
confidence: 67%
“…24 CRISPR-Cas system is a bacterial adaptive immune system protecting itself against invaders and has been used in several bacteria such as E. coli, 25 Staphylococcus aureus and Shewanella algae. 26,27 This system provided an effective strategy for sequence-specific curing of the plasmid.…”
Section: Discussionmentioning
confidence: 99%
“…are believed to be susceptible to most antibiotics used in human medicine, such as third-generation cephalosporins, gentamicin and ciprofloxacin [ 7 ]. However, recent studies have shown an increasing resistance of new isolates [ 1 , 13 , 14 ]. This resistance, in addition to the increasing number of infections, underscores the importance of research focusing on these bacteria and how to prevent new infections.…”
Section: Introductionmentioning
confidence: 99%